INDONESIAN NON-ENGLISH MAJOR STUDENTS’ VIEWS AND EXPERIENCES: DUOLINGO FOR LEARNING ENGLISH - Zumrudiana, Ainu; Syafitri, Nurul Intan; Lestari, Iin Widya; Zainuddin, Moh (STKIP Persada Khatulistiwa Sintang, 2024)
The research investigated non-English major students' views and perspectives on learning English through Duolingo. Qualitative methods were used, with 30 questionnaire items and 15 interview prompts to gather data on students' perception of using Duolingo to learn English, as well as the difficulties and obstacles they encountered. The participants were 41 undergraduate students in the sixth semester of the Early Childhood Education major at a university in Bojonegoro. This research focused on using Duolingo as a learning tool to enhance the teaching and learning process, considering the impact of technological advancements in education. The results showed that nearly 99% of participants viewed Duolingo as useful and functional. Challenges and obstacles in using the application for English learning were categorized into internal factors (mood, laziness, lack of knowledge, and time constraints) and external factors (network issues, smartphone usage, and application errors).Keywords: Duolingo application; learning English; English learning application; English learning media